An open-label pilot trial of N-acetylcysteine and varenicline in adult cigarette smokers. (January 2015) - McClure, Erin A.; Baker, Nathaniel L.; Gipson, Cassandra D.; Carpenter, Matthew J.; Roper, Amanda P.; Froeliger, Brett E.; Kalivas, Peter W.; Gray, Kevin M.
Abstract Background: Varenicline (VAR) has demonstrated superior efficacy over other smoking cessation pharmacotherapies, though 50–60% of those treated do maintain abstinence. Some preclinical findings suggest that new nicotine dependence pharmacotherapies should target the glutamatergic system, given its demonstrated role in addiction. Attention has been given to N-acetylcysteine (NAC), which appears to restore normal glutamate signaling in animal models. It is possible that NAC and VAR may work in concert to promote abstinence at higher rates than with either medication alone. Objective: To demonstrate the feasibility and safety of co-administering NAC and VAR in nicotine-dependent participants. Methods: Participants (n = 19) were daily cigarette smokers, and did not need to be seeking treatment. They received 4 weeks of open-label treatment with NAC (1200 mg twice daily) and VAR (1 mg twice daily, following titration) and were assessed weekly for adverse events (AEs), smoking, craving and withdrawal. Results: Sixteen participants reported a total of 40 AEs, and most were mild (88%). The most commonly reported AE was nausea (15%). Medication adherence, assessed via self-reports and pill counts, was excellent (98%). Exploratory analyses showed reductions in cigarettes per day, though point prevalence abstinence at the end of the study was low. Conclusions: These preliminary data provide the first demonstration of safety and feasibility of the co-administration of NAC and VAR in cigarette smokers. AEs were consistent with those typically reported for VAR and NAC. These data support future efficacy research on NAC and VAR for smoking cessation.